Comparison of the solar photocatalytic activity of ZnO-Fe2O3 and ZnO-Fe0 on 2,4-D degradation in a CPC reactor - Maya Treviño, María de Lourdes; Villanueva Rodríguez, Minerva; Guzmán Mar, Jorge Luis; Hinojosa Reyes, Laura; Hernández Ramírez, Aracely (Royal Society of Chemistry, 2015)
In this work a comparative study of the catalytic activity of ZnO–Fe2O3 and ZnO–Fe0 0.5 wt% materials was carried out in the degradation of 2,4-dichlorophenoxyacetic acid (2,4-D) as a commercial formulation Hierbamina®, using a compound parabolic collector (CPC) reactor. The catalysts were synthesized by the sol–gel method and characterized by X-ray diffraction, UV-Vis diffuse reflectance spectroscopy, Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The textural properties of solids were determined from N2 adsorption isotherms using the Brunauer–Emmett–Teller (BET) method. The incorporation of Fe0 onto ZnO was demonstrated by X-ray photoelectron spectroscopy analysis. The photocatalytic tests were performed at pH 7, using 10 mg L−1 of herbicide and 0.5 g L−1 of catalyst loading. The decay in herbicide concentration was followed by reversed-phase chromatography. A complete degradation of 2,4-D was achieved using ZnO–Fe0 while 47% of herbicide removal was attained with ZnO–Fe2O3 mixed oxide for an accumulated energy QUV ≈ 2 kJ L−1. The removal percentage of total organic carbon (TOC) during the solar photocatalytic process was superior using ZnO–Fe0, achieving 45% compared to the 15% obtained with the mixed oxide catalyst.